11 Eylül saldırıları ardından Amerikan medyasında milliyetçilik - Akıner, Nurdan (My University, 2004)
This PhD dissertation research focuses on how U.S. media have released the news about 9/ 11 Attacks. A propaganda analysis approach is applied to the following days' coverage of the 9/ 11 Attacks to The World Trade Center and Pentagon, with the aim of studying how the various national and international news contexts influenced the media discourse's relationship to the propaganda discourse after the attacks. This problematic is relevant for the current discussion on U.S. media and patriotism in connection with fairness of journalism. Furthermore, with this study the effects of disinformation and misinformation on hate crimes are explained. The findings of the research points out that the U.S. media have pumped jingoistic craze and general freedoms, freedom of expression were limited by Bush's government in U.S. aftermath of 9/ 11 Attacks.
Keywords: Milliyetçilik; Nasyonalizm; Siyasal bilimler (Siyaset bilimi); Siyasal ideolojiler; Toplum bilimleri